A comunicação digital nos territórios rurais: um estudo do canal “O Extensionista” no YouTube - Serafin, Renato de Melo (2025)
This original study aims to analyze data from lecture-style videos produced by the "O Extensionista" YouTube channel. The aim was to understand how digital platforms are transforming teaching methodologies and communication in rural areas. In the field of STS, this research demonstrates how technologies and social practices intertwine in rural extension. Dialogical communication in ATER Digital values local knowledge and concrete experiences, while engagement data highlights the importance of formats that respect cultural plurality and rural protagonism, promoting more inclusive and collective extension practices. The guiding question of the study was to understand how videos on the "O Extensionista" YouTube channel, as an ATER Digital initiative, promote engagement and contribute to the innovation and improvement of rural extension practices in Brazil. Furthermore, we sought to answer which attributes of the channel's videos influence public participation and engagement in digital rural extension initiatives. And how do the data on views, likes, and interactions on the channel's videos reflect the effectiveness of Digital ATER initiatives? The research is configured as an exploratory and descriptive investigation. In turn, the collected data were schematized and organized for quantitative analysis. The channel "O Extensionista" has over 96,000 subscribers, has published over 6,800 videos, and has received over 34 million views. The sample for analysis comprises 75 videos generated on the channel from weekly live streams discussing topics related to digital ATER, research, and rural extension worker training. The videos in the sample under investigation have 21,967 views, 1,880 likes, and 1,893 interactions in the chat as their main metrics. The data was organized and categorized by speaker profile, gender, time period, talk/live stream duration, and language. The analyses were constructed using descriptive statistical parameters such as arithmetic mean, standard deviation and coefficient of variation. The most discussed topics were "Scenarios: Challenges and Opportunities in ATER (24%)" and "Technology and Innovation in Rural Extension (22.67%)". The topic with the highest average number of views was "Public Policies, Planning and Regulation of ATER (374)". The most common speaker profile is characterized by rural extensionists and males.